Water Conservation Planning at Telkom University Landmark Tower Bandung Campus - Bizantio Wiranta Ranadipura; Eka Wardhani (Universitas Diponegoro, 2021)
Telkom University makes efforts in developing higher education facilities and capacities by constructing new campus buildings. One of the supports for improving services is sanitation infrastructure in the form of installations consisting of clean water installations, wastewater installations and ventilation, and rainwater installations with the concept of installed clean water. Each building that will be built in the area of West Java Province applies the concept of green buildings and conservation air as regulated in the Regional Regulation of West Java Province 13 of 2013 concerning Buildings, including campus building builders so that business actors are required to implement water management which aims to maintain quality, quantity, and continuity of clean water in West Java Province. The implementation of the installation with the concept of green buildings and air conservation is carried out at the Telkom University Landmark Tower building, which aims to use clean water in the building which can be more efficient because the location of the building is in a clean water distress zone based on the basin map of West Bandung Regency. The implementation of water conservation that is planned is WAC-3 waste water recycling (water recycling) which can be used as a rinse and watering the garden. Construction of infiltration wells which functions to reduce rainwater runoff and increase groundwater reserves, WAC-5 rainwater storage (rainwater storage) which can be used as alternative raw water. The use of the WAC-2 water-saving sanitary device (water feature) uses water usage and PDAM water costs. The application of air conservation that ignores water is 17.5% in the dry season and 61.5% in the rainy season of the clean water need total.